Impelemtasi Kebijakan Identitas Kependudukan Digital di Kota Palu - Khairunnisah, Indah; Riadi, Slamet; Mufti, Moh Irfan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study aims to determine how the implementation of the Digital Population Identity (IKD) policy is carried out in Central Sulawesi Province. In this research, the author uses Edward III's theory (Widodo,2010:96), which consists of the criteria of Communication, Resources, Disposition, and Bureaucratic Structure. The research method used is descriptive qualitative research. Data collection was conducted using observation, documentation, and interviews. The selection and number of informants in this study used a purposive sampling technique, targeting parties considered to have in-depth knowledge regarding the research problem, totaling four (4) people. The data analysis techniques include data collection, data presentation, data condensation, and drawing conclusions/verification. Based on the results of this research, it can be concluded that there are several issues that require special attention, namely: lack of massive socialization, resulting in insufficient comprehensive information to the public regarding IKD; limited technology access, such as dependency on owning gadgets and data packages as well as limited internet access in some areas; and the fact that IKD has not yet become a requirement in many public services, causing the public to not feel the urgency to activate it. In addition, the existing facilities and infrastructure are still inadequate, thus this policy cannot yet be implemented optimally.